2001
DOI: 10.1007/s002560100322
|View full text |Cite
|
Sign up to set email alerts
|

Tendon involvement in rheumatoid arthritis of the wrist: MRI findings

Abstract: Low grades of peritendinous effusion were more common in the volar compartment whereas moderate and high degrees of tendon sheath fluid collection and/or pannus and signs of tendonitis were more frequent in the dorsal and ulnar tendon sheaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…This incidence was much higher than was reported in other cohorts in the literature [25][26][27], which indicated the presence of tenosynovitis in approximately 50-60 % of included patients. In a group of 50 patients with early, untreated RA, Wakefield et al [36] found flexor tenosynovitis in 82% of patients with MRI and in only 48% of patients with US.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This incidence was much higher than was reported in other cohorts in the literature [25][26][27], which indicated the presence of tenosynovitis in approximately 50-60 % of included patients. In a group of 50 patients with early, untreated RA, Wakefield et al [36] found flexor tenosynovitis in 82% of patients with MRI and in only 48% of patients with US.…”
Section: Discussioncontrasting
confidence: 51%
“…Some studies regarding US incidence [25][26][27], validity [13] and inter-observer reliability of US detection of tenosynovitis involving multiple investigators [28][29][30][31] have been performed. Tenosynovitis has been included together with synovitis without separation between joints and tendons' pathology in some described US scores [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting point of difference between lupus-associated Jaccoud's arthropathy and RA is that the flexor tendons are more often involved in the 748 McQUEEN ET AL former condition, as opposed to extensor tendons in the latter (20). Although we did not investigate healthy subjects in this study, MRI scans from normal subjects have been studied by others (3,10). Small amounts of fluid in 1 or more dorsal wrist compartments have been described, with rare examples of increased signal intensity within the substance of tendons, but pannus has not been identified.…”
Section: Discussionmentioning
confidence: 93%
“…Hypertrophy of the tenosynovium within the tendon sheath is revealed as bright signal in thickened tissue surrounding a tendon on T1-weighted postcontrast and T2-weighted sequences, while an accompanying effusion within the sheath is low signal on early T1-weighted postcontrast scans. Changes within the tendon itself can be identified and include increased signal on T2-weighted images implying inflammatory change, as well as thinning and attenuation, which are likely to precede rupture (7,10). MRI identification of tendon rupture is highly correlated with surgical confirmation and has been shown to be more accurate than clinical evaluation (3).…”
mentioning
confidence: 99%
“…Clinical evaluation of tenosynovitis is difficult and conventional radiography is not useful. MRI is a technique that allows good visualisation and assessment of inflammatory changes in the tendons and tendon sheaths 2 3…”
Section: Introductionmentioning
confidence: 99%